Utilizing action research to integrate curriculum, instruction, and assessment in middle school classrooms. Issue 3 (27th May 2022) - Monem, Ruba; Cramer, Elizabeth D.
Abstract: Action research is an evidence-based practice that is highly applicable to middle school teaching and learning. Middle school teachers can empower themselves and their students by participating in immersive, meaningful activities that are designed to improve educational outcomes. Action research is purposeful and beneficial for teachers, students, and educational stakeholders. This article describes the features and phases of action research and how the framework can be used to find solutions to classroom concerns.